The causal effect of family physician program on the prevalence, screening, awareness, treatment, and control of hypertension and diabetes mellitus in an Eastern Mediterranean Region: a causal difference-in-differences analysis - Neda Mohammadi; Ahad Alizadeh; Sahar Saeedi Moghaddam; Erfan Ghasemi; Naser Ahmadi; Mehdi Yaseri; Negar Rezaei; Mohammad Ali Mansournia (BMC Public Health, 2023)
Hypertension (HTN) and diabetes mellitus (DM) as part of non-communicable diseases are among the most common causes of death worldwide, especially in the WHO's Eastern Mediterranean Region (EMR). The family physician program (FPP) proposed by WHO is a health strategy to provide primary health care and improve the community's awareness of non-communicable diseases. Since there was no clear focus on the causal effect of FPP on the prevalence, screening, and awareness of HTN and DM, the primary objective of this study is to determine the causal effect of FPP on these factors in Iran, which is an EMR country. We conducted a repeated cross-sectional design based on two independent surveys of 42,776 adult participants in 2011 and 2016, of which 2301 individuals were selected from two regions where the family physician program was implemented (FPP) and where it wasn't (non-FPP). We used an Inverse Probability Weighting difference-in-differences and Targeted Maximum Likelihood Estimation analysis to estimate the average treatment effects on treated (ATT) using R version 4.1.1. The FPP implementation increased the screening (ATT0.167em=0.167em36%, 95% CI: (27%, 45%), P -value0.167em<0.167em0.001) and the control of hypertension (ATT0.167em=0.167em26%, 95% CI: (1%, 52%), P -value0.167em=0.167em0.03) based on 2017 ACC/AHA guidelines that these results were in keeping with JNC7. There was no causal effect in other indexes, such as prevalence, awareness, and treatment. The DM screening (ATT0.167em=0.167em20%, 95% CI: (6%, 34%), P -value0.167em=0.167em0.004) and awareness (ATT0.167em=0.167em14%, 95% CI: (1%, 27%), P -value0.167em=0.167em0.042) were significantly increased among FPP administered region. However, the treatment of HTN decreased (ATT0.167em=0.167em-32%, 95% CI: (-59%, -5%), P -value0.167em=0.167em0.012). This study has identified some limitations related to the FPP in managing HTN and DM, and presented solutions to solve them in two general categories. Thus, we recommend that the FPP be revised before the generalization of the program to other parts of Iran.
Keywords: 300; Family physician program; Hypertension; Diabetes mellitus; Diference-in-diference; TMLE; Iran